Optimization Of Branding And Digital Marketing: Innovative Strategies to Improve The Competitiveness of Small and Medium Enterprises P roducing Banana Chips (In The Village of Pakenjeng) - Auladinnursoba, Alvi; Hibatul Azizi, Moch Farhan (Indonesian Journal of Community Empowerment (IJCE), 2024)
This research aims to optimize the branding and digital marketing of UMKM Banana Chips "Teh Enda" in Pakenjeng Village with innovative strategies. With the increasingly fierce competition in the banana chips market, these UMKM face challenges in attracting buyers, especially because of the many similar products circulating in the market. This research focuses on implementing branding and digital marketing strategies using the Instagram platform to increase product competitiveness. Through the stages of problem identification, product labeling, social media marketing strategy development, and digital marketing implementation, the KKN team strives to strengthen the brand position and expand the market reach of UMKM. The results of this implementation are expected to make a significant contribution to increasing sales and brand awareness of "Teh Enda" Banana Chips.